The Successful Teacher’s Verbal Cues in View of Interpersonal Communication to Lead EFL Adult Beginner Learner’s Accuracy in Calling Interaction - Nurul Hatifah (Universitas Negeri Makassar, 2017)
The objectives of the research are to give descriptive account of (1) the successful teacher’s verbal cue leading the adult beginner learner’s accuracy via calling interaction and (2) the learner’sperception of the teacher’s verbal cues leading her accuracy. This research applied descriptive qualitative research. By using purposive sampling technique, one teacher and one adult learner of White House Indonesia, English institution, were chosen as the research objects. The data regarding with teacher’s verbal cues in view of interpersonal communication used in calling interaction were collected by recording voice by using Voice Call Recorder, and semi-structured interview obtained the data regarding with the learner’s perception of the teacher’s verbal cues. The results revealed that (1) verbal indirect cue covering recalling cue, clarifying cue, associating cue and exemplifying cue, and verbal direct cue covering recalling cue and clarifying cue were the typically successful verbal cues used by the teacher to lead the adult beginner learner’s accuracy. (2) The teacher’s verbal cues were helpful to lead the learner’s accuracy in term of pronunciation, vocabulary, and grammar in calling interaction. Therefore, it can be concluded that the teacher’s verbal cues could facilitate the learners to respond the teacher’s questions accurately since the teacher and learners were involved in interpersonal communication. Keywords: Verbal cues, interpersonal communication, English accuracy.